Potential of Lantana camara Linn. Weed against Wood Destroying Fungi - Tripathi, Sadhna; Rawat, Kanchan; Dhyani, Swati; Pant, Himani (Indian Forester, 2009)
Lantana camara Linn. belonging to family Verbenaceae is known world wide as an obnoxious weed having 650 varieties and spreading over 60 countries. The present study was carried out to investigate the efficacy of L. camara extracts against wood destroying white and brown rot fungi. Root, stem and leaves of Lantana were collectively extracted with ethanol followed by hot water. Ethanolic extract at a concentration levels of 0.005, 0.01, 0.05, 0.1, 0.15, 0.2, 0.5, 1.0, 1.5 and 2.0% and the hot water extract at a concentration levels of 0.5, 1.0, 2.0 and 3% were tested against Trametes versicolor, a white rot and Oligoporus placentus, a brown rot by malt-agar bioassay. Results revealed that the ethanolic extract upto 0.01% concentration level recorded 0% growth of T. versicolor and O. placentus as compared to 100% observed in control plates. A growth of 50 and 28% of O. placentus and T. versicolor was observed at 0.005% concentration of the ethanolic extract. Hot water extract on the other hand at all the concentrations tested recorded 97 to 100% surface coverage of the test fungi. Qualitative analysis of the ethanolic and hot water extracts revealed presence of high amounts of phenolics and alkaloids and appreciable amount of terpenoids in the ethanolic extract. Presence of high amounts of carbohydrates and trace amounts of alkaloids and phenols were observed in hot water extract.